Preliminary Evidence on Guided Imagery and Music (GIM) for Reducing Pain Intensity in Women with Primary Dysmenorrhea - Mutiara Nur Jasynda; Ahmad Ridfah; Novi Yanti Pratiwi; Jasman (Universitas Ahmad Dahlan, 2026)
This study aimed to evaluate the potential of Guided Imagery and Music (GIM) as a non-pharmacological intervention for reducing pain intensity in individuals with primary dysmenorrhea. A quasi-experimental one-group pretest–posttest design with follow-up was employed involving seven female participants aged 20–24 years. Pain intensity was measured using the Visual Analogue Scale (VAS) across three time points. The Friedman test indicated a significant difference in pain intensity over time (χ²(2) = 12.08, p = 0.002). Post hoc Wilcoxon Signed-Rank tests revealed significant reductions from pretest to posttest (Z = -2.392, p = 0.017) and from pretest to follow-up (Z = -2.388, p = 0.017). These findings suggest that GIM is associated with reduced menstrual pain intensity and may offer preliminary promise as a complementary intervention. However, given the small sample size, absence of a control group, and reliance on self-reported outcomes, the results should be interpreted as pilot evidence. Further research using more rigorous experimental designs and larger samples is warranted to establish the efficacy of GIM.